Ni/Al2O3 spherical catalysts produced by magnetron sputtering - dos Santos A.M. (2022)
© 2022 Elsevier LtdThis paper discusses the development of Ni-covered alumina catalysts by the magnetron sputtering. Thin films of magnetron sputter Ni were deposited on alumina spherical substrates as a function of the deposition time with and without the substrate previously coated by washcoating. For comparison purposes, samples were prepared by washcoating alumina spherical substrates with an alumina porous layer impregnated with Ni. Catalysts were characterized by scanning electron microscopy with field emission gun, X-ray diffraction, Raman spectroscopy, energy dispersive spectroscopy, X-ray photoelectron spectroscopy, and vibrating sample magnetometry. The catalytic activity was evaluated from the decomposition of methylene blue solution and characterized by optical spectrophotometry. Results show that the catalyst produced by the impregnation route presents a high concentration of Ni oxides, irregular Ni layer, and lower catalytic activity when compared to catalysts produced through magnetron sputtering. Thin Ni films deposited by magnetron sputtering without the washcoating layer present a high concentration of metallic Ni, more uniform film distribution, high catalytic activity, and ferromagnetic behavior. This latter property associated with the small mass of the alumina sphere allows controlling the motion of the spheres in aqueous solutions by applying external magnetic fields.